Costs of Informal Caregiving in Dementia - Pires, Cátia Luz (2020)
Introduction: From a perspective that considers the costs borne by the informal caregiver and the care-recipient, this study quantifies and values the use of health and social services, and the time dedicated to caregiving in dementia situations.Material and Methods: Sociodemographic information and use of services was obtained from 123 caregiving dyads. Costs with informal care were evaluated and valued considering the Health Sector (health services), Patient/Family Sector (time of caregiving) and Other Sectors (social services, continuous care, other private services). Costs with health and social services considered the paying person; the Patient/Family Sector was valued through the proxy-good method. The costs were calculated per month and the value for 100 dyads.Results: The total cost of informal care was €61 982.2/month per 100 dyads. The Patient/Family Sector value (€44 030.0/month) contributed with 71.0% of the total costs, Other Sectors with 20.8% (€12 887.4/month), and the Health Sector with 8.2% (€5064.8/month).Discussion: The obtained value per dyad (€619.8/month) represents 77.5% of their monthly income (median = €800.0; interquartile range = 679.0), which can limit the decision of continuing the care provision at home. Considering the values presented for this specific sample, it is estimated that the exemption of fees in the Health Sector and/or benefits in social services may contribute to a downward estimate of the costs.Conclusion: Regardless of the complexity in estimating the costs associated with informal caregiving in dementia, this paper provides some insights on the burden they can represent for the family income.